Alternative Licensure Curriculum from KansansCan Redesign Gemini Schools - Kevin L Splichal (The Advocate, 2019)
The purpose of this reflection paper is to encourage Educational Preparation Providers (EPPs) to partner with KansansCan Redesign Gemini schools to evaluate EPP curriculum through personal interviews with alternative licensure teachers in KansansCan Redesign schools. Curriculum, implemented by the EPP, should take into consideration the experiences of those for whom it is designed and tailor pedagogical instruction to better match current practices in Gemini redesign schools. Personal interviews with candidates will provide experience-based evidence for analysis and consideration by EPPs.
Keywords: Alternative Licensure; Providing Institutions; EPPs; Teacher Preparation; KansansCan; Redesign; Curriculum